Spatial and temporal distribution of Bursaphelenchus xylophilus inoculated in grafts of a resistant clone of Pinus thunbergii. Issue 2 (4th March 2019) - Nakajima, Gou; Iki, Taiichi; Yamanobe, Taro; Nakamura, Katsunori; Aikawa, Takuya
ABSTRACT: Preventive plantation of resistant Pinus thunbergii seedlings is anticipated in non-epidemic areas of pine wilt disease (PWD) in Japan. The scions of resistant clones, which are required to establish a seed orchard for the production of resistant seedlings, might harbor Bursaphelenchus xylophilus (a pathogen of PWD), as they are grown in epidemic areas and artificially inoculated with B. xylophilus to verify their resistance. In this study, we analyzed within-tree distribution of B. xylophilus in inoculated grafts of a resistant P. thunbergii clone, Yuza-155, at two different times, 7 and 19 months after inoculation. Experimental evidence using both direct extraction of nematodes and a DNA-based detection technique demonstrated that the migration and propagation of inoculated nematodes were restricted mostly within the scion stems and rootstocks. In branch samples, nematodes were detected less frequently by the DNA-based method and no live nematodes were extracted at 7 months after inoculation, whereas at 19 months after inoculation, neither of the methods detected any nematodes. Thus, the probability that the current-year shoots of this resistant clone, Yuza-155, which initiated plant growth in the season following inoculation, are infected with B. xylophilus is quite low. Therefore, they may serve as pathogen-free scions for propagation of ramets of resistant P. thunbergii clones and construction of seed orchards in PWD non-epidemic locations.